2012
DOI: 10.1111/tpj.12029
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete transfer of accessory loci influencing SbMATE expression underlies genetic background effects for aluminum tolerance in sorghum

Abstract: SUMMARYImpaired root development caused by aluminum (Al) toxicity is a major cause of grain yield reduction in crops cultivated on acid soils, which are widespread worldwide. In sorghum, the major Al-tolerance locus, Alt SB , is due to the function of SbMATE, which is an Al-activated root citrate transporter. Here we performed a molecular and physiological characterization of various Alt SB donors and near-isogenic lines harboring various Alt SB alleles. We observed a partial transfer of Al tolerance from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 58 publications
6
53
0
Order By: Relevance
“…consistent with other plant MATE transporters that upon expression produce anion currents in X. laevis oocytes (Maron et al, 2010;Melo et al, 2013). Our experiments do not exclude a role for RHC1 in CO 2 signaling (Tian et al, 2015) but point to the need to investigate whether previous findings might result at least in part from additive currents mediated by SLAC1 and RHC1.…”
Section: Discussionsupporting
confidence: 68%
“…consistent with other plant MATE transporters that upon expression produce anion currents in X. laevis oocytes (Maron et al, 2010;Melo et al, 2013). Our experiments do not exclude a role for RHC1 in CO 2 signaling (Tian et al, 2015) but point to the need to investigate whether previous findings might result at least in part from additive currents mediated by SLAC1 and RHC1.…”
Section: Discussionsupporting
confidence: 68%
“…However, normal frequency distributions in sorghum crosses where the Al resistance locus Alt SB plays a role in Al PP66CH23-Kochian ARI 15 January 2015 11:1 resistance (70) and the presence of apparent transgressive segregation suggest that a more complex inheritance pattern takes place in sorghum (9). Further support for this assertion is based on the incomplete transfer of Al resistance from parents to near-isogenic lines that has been observed in both sorghum (77) and wheat (40, 123). Additionally, in wheat, Ryan et al (110) have reported a second Al resistance mechanism (in addition to TaALMT1-mediated malate release) that involves citrate exudation controlled by a MATE homolog, indicating that there is more diversity in wheat Al resistance than initially thought.…”
Section: The Genetic Basis For Crop Aluminum Resistancementioning
confidence: 85%
“…Most importantly, the detection of transgressive segregation suggests that different Al resistance genes may act additively to result in high levels of sorghum Al resistance. A strong correlation has been found between SbMATE expression and Al resistance in sorghum (71,77), and additional loci acting via transcriptional regulation of SbMATE seem likely to play a role in sorghum Al resistance. When Melo et al (77) used marker-assisted backcrossing to transfer only the Alt SB locus from tolerant donors into an Alsensitive recurrent parent, they observed incomplete transfer of the Al resistance phenotype as well as reduced SbMATE expression in the derived near-isogenic lines harboring the Al-tolerant Alt SB alleles.…”
Section: Sorghummentioning
confidence: 93%
See 1 more Smart Citation
“…Although the mechanisms regulating the expression level of ALMT and MATE/AACT have been elucidated in some species as described above, the whole picture on how these genes are regulated in different species and cultivars, remains to be further investigated in detail. Recently, Melo et al (2013) found that introduction of SbMATE into different background resulted in different expression level and Al tolerance, suggesting that SbMATE expression is regulated at multiple levels. It seems that both cis-and trans-acting elements are involved in regulating SbMATE expression.…”
Section: Prospectivementioning
confidence: 99%